Personal Branding of Tegal District Head Candidates in Increasing Electability on Social Media Instagram - Pratiwi, Cindy; Zainudin, Arif; Widodo, Agus Setio (Universitas Muhammadiyah Ponorogo, 2024)
In this era of globalization social media especially Instagram is a platform that is widely used by political actors in introducing their personal branding to attract public attention. Personal branding strategy is a good step in building political communication with voters due to affordability during the campaign. So in this paper the author wants to reveal what personal branding strategies are carried out by the candidates. This article is analyzed using a political branding approach using orange data mining as a coding tool to find out the sentiment of the public. The data from this study were taken from several posts from each candidate and comments from Instagram users. The results of this study show that the branding carried out by the two candidates shows a predominantly neutral sentiment from the public against several comments made in the comments column.